EFEKTIVITAS PROGRRAM PENGEMBANGAN DESTINASI PARIWISATA OLEH DINAS PARIWISATA KEBUDAYAAN KEPEMUDAAN DAN OLAHRAGA KABUPATEN SUMEDANG - Sudrajat, Karen Zein (LPPM UNSAP & FISIP UNSAP, 2024)
Every local government strives to optimize the potential within its respective region, and one of the efforts is to develop the tourism sector. Responsible for the tourism development program is the Department of Tourism, Culture, Youth, and Sports. The Tourism Department itself has programs aimed at developing existing tourist attractions; each program's effectiveness must be measured. Program effectiveness refers to the extent to which a program achieves its predetermined goals and delivers expected outcomes in the social, economic, or environmental contexts targeted. Therefore, this research aims to investigate the Effectiveness of the Tourism Destination Development Program by the Department of Tourism, Culture, Youth, and Sports of Sumedang Regency. This study employs a qualitative method, utilizing data collection techniques through literature review, field study, and triangulation. Informants are selected using purposive sampling, resulting in four informants. Data processing procedures include data reduction, data presentation, and drawing conclusions. Based on the research findings, it can be concluded that the Effectiveness of the Tourism Destination Development Program by the Department of Tourism, Culture, Youth, and Sports of Sumedang Regency is still hindered in its implementation. This includes challenges such as inadequate staffing and the lack of tourism knowledge among employees, insufficient information availability for the public, and various obstacles both internal and external to the tourism department. Additionally, several recommendations are proposed that could be prioritized for development considerations.